Motion and Context Sensing Techniques for Pen Computing - Hinckley, Ken; Benko, Hrvoje; Chen, Xiang ‘Anthony’ (GI '13 Proceedings of Graphics Interface 2013, 2013)
We explore techniques for a slender and untethered stylus prototype enhanced with a full suite of inertial sensors (three-axis accelerometer, gyroscope, and magnetometer). We present a taxonomy of enhanced stylus input techniques and consider a number of novel possibilities that combine motion sensors with pen stroke and touchscreen inputs on a pen + touch slate. These inertial sensors enable motion-gesture inputs, as well sensing the context of how the user is holding or using the stylus, even when the pen is not in contact with the tablet screen. Our initial results suggest that sensor-enhanced stylus input offers a potentially rich modality to augment interaction with slate computers.